Effects of recovery program psychopedagogical in students with learning difficulties of elementary schools, Huánuco - 2011 - Campos C., Lilia (2013)
The study has been aimed at determining the effects of a recovery program in educational psychology students with learning difficulties of Primary Education Institutions Huanuco for which as shown has 61 students with learning difficulties Educational Institutions Primary Huanuco. Was taken as a sample to 61 students in first through sixth grade who have been applied programs according to the identified challenges, we worked with teachers who implemented the programs in the classroom and parents who were trained to accompany school their children.